Handbook of research on leadership and creativity - Mumford, Michael D.; Hemlin, Sven, 1948- (Cheltenham, UK : Edward Elgar Publishing, 2017)
The rapid pace of technological change and globalization of products, competition and services have conspired to place a new premium on innovation for firms across the world. Although many variables influence creativity and innovation, the effective leadership of creative teams has proved especially important. This timely Handbook presents the state of the art for what leaders must do to lead creative teams and how they should do it.
Includes bibliographical references and index.
Keywords: Leadership -- Handbooks, manuals, etc; Creative ability -- Handbooks, manuals, etc